2018
DOI: 10.11607/prd.3033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polishing System on the Surface Roughness of Flowable and Regular-Viscosity Bulk Fill Composites

Abstract: This study evaluated the influence of polishing protocols on the surface roughness of flowable and regular bulk fill composites. Five bulk fill composites were tested: SureFil SDR Flow (SDR), Tetric EvoFlow Bulk fill (TEF), Filtek Bulk Fill Flowable (FIF), Tetric EvoCeram Bulk Fill (TEC), and Filtek Bulk Fill Posterior (FIP). Two polishing protocols were tested: Sof-Lex and Astropol. Astropol created a smoother surface for FIP (P < .05); however, the polishing protocol did not influence surface roughness on TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 24 publications
3
27
0
1
Order By: Relevance
“…In the current study, bulk‐fill composites showed greater surface roughness values when compared with NRBCs in all groups. Previous studies have reported two to sevenfold greater surface roughness for bulk‐fill composites compared with NRBCs, which lend support our findings (Lassila, Dupont, Lahtinen, Vallittu, & Garoushi, 2020; O'Neill et al, 2018; Rigo et al, 2018; Theobaldo et al, 2020). Increasing filler particle size to increase translucency of the bulk‐fill composites to achieve application of the composite as a single layer of 4 mm may result in increased surface roughness (Bucuta & Ilie, 2014; Fronza et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, bulk‐fill composites showed greater surface roughness values when compared with NRBCs in all groups. Previous studies have reported two to sevenfold greater surface roughness for bulk‐fill composites compared with NRBCs, which lend support our findings (Lassila, Dupont, Lahtinen, Vallittu, & Garoushi, 2020; O'Neill et al, 2018; Rigo et al, 2018; Theobaldo et al, 2020). Increasing filler particle size to increase translucency of the bulk‐fill composites to achieve application of the composite as a single layer of 4 mm may result in increased surface roughness (Bucuta & Ilie, 2014; Fronza et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have reported that surface roughness of composites is more closely related to the material composition than the polishing system used and that a particular polishing system may not perform equally with all composite resins (Rigo et al, 2018; St‐Pierre et al, 2019). Filler particles are one of the many factors affecting the properties of composite resins.…”
Section: Discussionmentioning
confidence: 99%
“…After each cup used, air/water jets were applied 10 s apart at a distance of 10 cm to remove debris left by the abrasives and the specimen was then air‐dried for 5 s (Adapted from Magdy, Kola, Algahtani, & Algahtani, ). The specimens that were submitted to the additional polishing were previously given the finishing and polishing described above, added to the use of the Astrobrush, with circular movements in each specimen, with low speed (10,000 rpm) for 15 s each (Rigo et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Filtek™ Bulk Fill and Filtek™ Z250 have higher filler loading (58.4% and 60%, respectively), compared to Fill-Up™ (49%), which also correlates with lower surface roughness values. According to previous studies, the surface roughness is lowered by decreasing the filler size and increasing the overall filler content [ 30 , 31 ]. Filtek™ Bulk Fill can match the traditional, incremental-fill Filtek™ Z250 in surface roughness values, as no differences were found in the estimated means pooled from the different polishing procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Filtek™ Bulk Fill can match the traditional, incremental-fill Filtek™ Z250 in surface roughness values, as no differences were found in the estimated means pooled from the different polishing procedures. Bulk-fill composites feature changes in their organic matrix, filler content, and/or size [ 30 , 32 ]. Usually, manufacturers increase the depth of cure by enhancing the material’s translucency.…”
Section: Discussionmentioning
confidence: 99%